The association of erectile dysfunction with productivity and absenteeism in eight countries globally. Issue 11 (6th August 2019) - Goldstein, Irwin; Goren, Amir; Li, Vicky W.; Maculaitis, Martine C.; Tang, Wing Yu; Hassan, Tarek A.
Abstract: Aim: To evaluate the association of erectile dysfunction (ED) with work productivity loss, activity impairment and health‐related quality of life (HRQoL) across Brazil, China, France, Germany, Italy, Spain, the UK and the US. Methods: This cross‐sectional observational study used data from adult men (40‐70 years old; N = 52 697) from the 2015 and 2016 National Health and Wellness Surveys. ED assessment was based on self‐reported difficulty in achieving or maintaining an erection in the past 6 months. Impairment to work and non‐work activities and HRQoL were assessed for each country and compared against the US. Multivariable models tested interactions between ED status and country for each outcome. Results: Overall ED prevalence was reported as 49.7%, with Italy reporting the highest rate (54.7%). Men with ED reported significantly higher absenteeism (7.1% vs 3.2%), presenteeism (22.5% vs 10.1%), overall work productivity impairment (24.8% vs 11.2%), activity impairment (28.6% vs 14.5%) and significantly lower Mental Component Summary scores (MCS; 46.7 vs 51.2), Physical Component Summary scores (PCS; 48.3 vs 53.0), and health state utilities (SF‐6D: 0.693 vs 0.778; all, P  < 0.001) than men with no ED. After adjusting for covariates, compared with the US, the association of ED status with overall work productivity impairment was greatest in the UK (26% higher; P  < 0.05), and with MCS, PCS and SF‐6D scores was greatest in China (−2.67, −1.58, and −0.043 points, respectively; all, P  < 0.001). Greater ED severity was significantly associated with higher impairment to work and non‐work activities and lower HRQoL, with China reporting the highest burden, compared with the US (most P  < 0.05). Conclusion: ED poses a significant burden with respect to work productivity and HRQoL, with greater severity associated with worse outcomes. Better management and earlier detection may help reduce this burden, especially in countries reporting a strong association between ED and poor economic and health outcomes.